Addressing Environmental, Economic and Social Impact Mining Companies on Taliabu Island, North Maluku - Sitorus, Suryadi; Wiyarni, Wiyarni (Technium Social Sciences Journal, 2024)
The fundamental characteristic of the iron ore mining industry is clearing land and changing the natural landscape so that it has the potential to have an impact on the environment, social and economic aspects of society. This research was conducted to determine the environmental, social and economic impacts on the people of Taliabu Island Village. This research uses a qualitative method with a case study method. The conclusion of this research is that the environmental impact caused by mining in the Taliabu Island Village area can still be overcome by the company by replanting trees in places where mining has been completed and the company even provides signs along roads and dangerous areas so that the community is protected from these environmental impacts. . The company can also overcome the social impacts that arise by providing equal career development opportunities for local employees and migrant employees so that social jealousy does not occur and economic welfare increases for the people of Taliabu Island Village. The community’s economy has improved with the opportunity to work as company employees and the emergence of many food stalls, daily necessities stalls and even entertainment venues where previously the community had a source of income from clove and head plantations. The company also establishes a family relationship between the village head and all members of the community so that the impact, no matter how small, can still be overcome because all levels of society have a sense of ownership of the company and the benefits of the company are greatly felt.